Death run - Higgins, Jack, 1929-; Richards, Justin (London HarperCollins, 2008)
A mafia banker with access to a large number of criminal accounts is willing to give evidence in exchange for help retiring from the mob, but when spy John Chase assists him, he puts his fifteen-year-old twins, Rich and Jade, in the line of fire.
Keywords: Chance, Jade (Fictitious character); Chance, Rich (Fictitious character); Spies -- Fiction; Organized crime -- Fiction; Fathers -- Fiction; Twins -- Fiction; Brothers and sisters -- Fiction; Adventure and adventurers -- Fiction; Venice (Italy) -- Fiction; Italy -- Fiction; England -- Fiction